Knowing antimicrobial resistance in practice: a multi-country qualitative study with human and animal healthcare professionals. Issue 1 (1st January 2019) - Pearson, Maddy; Chandler, Clare
ABSTRACT: Background : Antimicrobial resistance (AMR) is a growing global problem. Raising awareness is central to global and national action plans to address AMR in human and livestock sectors. Evidence on the best ways to reduce antibiotic use, and the impact of awareness raising activities is mixed. This paucity of evidence is acute in Low-Middle-Income Country (LMIC) settings, where healthcare professionals who prescribe and dispense antimicrobial medicines are often assumed to have limited awareness of AMR and limited knowledge of the optimum use of antimicrobials. Objectives : This research aimed to explore AMR awareness among human and animal healthcare professionals and the contextual issues influencing the relationship between awareness and practices of antimicrobial prescribing and dispensing across different LMIC settings. Methods : Qualitative interviews and field observations were undertaken in seven study sites in Ethiopia, India, Nigeria, the Philippines, Sierra Leone and Vietnam. Data included transcripts from interviews with 244 purposively sampled healthcare professionals, analysed for cross-cutting themes. Results : AMR awareness was high among human and animal healthcare professionals. This awareness of AMR did not translate into reduced prescribing and dispensing; rather, it linked to the ready use of next-line antibiotics. Contextual factors that influenced prescribing and dispensing included antibiotic accessibility and affordability; lack of local antibiotic sensitivity information; concerns over hygiene and sanitation; and interaction with medical representatives. Conclusions : The high awareness of AMR in our study populations did not translate into reduced antibiotic prescribing. Contextual factors such as improved infrastructure, information and regulation seem essential for reducing reliance on antibiotics.